Courting Social Justice Judicial Enfotcement of Social and Economic Rights in the Developing World - Gauri, Varun (Cambridge University Press, 2013)
This book was conceived as an effort to join three streams of inquiry. First, ever since the mid- to late-1990s, when governance became a development priority, scholars and policy makers have sought institutional reforms to make governments more accountable for failures to provide basic services and alleviate poverty. Second, many of the innovative constitutions that emerged around the time of the “third wave” of democratization, as well as developments in legal and political theory, blurred the once bright-line distinction between negative and positive rights, with the consequence that legal or quasi-legal accountability for social and economic performance became more attractive. And third, studies in judicial politics have elaborated frameworks for assessing the causes and consequences of the legalization of political demands. Simply put, the time had come for a book on the role and impact of courts in fulfilling social and economic rights in the developing world.